Urbanization And Social Change In Ambon City: Challenges And Opportunities For Local Communities - Yamres Pakniany (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2024)
This research discusses the impact of migration on social change in Ambon City, Indonesia. Ambon City, as the economic and cultural center of the Maluku region, has undergone significant transformation due to migration, both internal and external. This research uses a descriptive qualitative approach through literature study. The results of this study outline how migration has created challenges in terms of social integration, changes in cultural identity, and the potential for social conflict. On the other hand, migration also brings opportunities in the form of economic growth, cultural diversity, and cross-cultural innovation. To overcome these challenges, the Ambon City government needs to formulate policies that support social inclusion, sustainable economic development, and preservation of cultural identity. Collaboration between natives and migrants should also be enhanced to create a harmonious and competitive environment, ensuring that Ambon City remains an attractive and diverse place for all its residents. This research underscores the importance of an in-depth understanding of migration dynamics and social change to capitalize on migration opportunities while maintaining the social, economic and cultural sustainability of Ambon City.